(untitled) (Acta Scientiarum. Animal Sciences, 2017)
An experiment was conducted to evaluate the feeding behavior of feedlot-finished bulls and cull cows in the Cerrado region of Piauí State, Brazil. Forty Zebu cattle were used, of which 20 steers averaging 283.0 ± 20.82 kg initial body weight and 30 months of age; and 20 cull cows averaging 296.1 ± 17.80 kg initial body weight and 100 months of age. Animals were grouped according to the following treatments: bulls and cull cows, using a completely randomized design. Feeding behavior was evaluated by means of visual observations every five minutes during 24h. Results were subjected to analysis of variance by the F test (p < 0.05) using the System for Statistical and Genetic Analysis - SAEG (version 9.1). The feeding behavior was expected not to affect the feed intake of cull cows and bulls, so that feed management can be the same for both categories. For all variables, there were differences between the categories (p > 0.05), showing that feeding behavior is influenced by the cattle category.